Catalogue of super-trees in Istria (Croatia) created as a result of the citizen science action - Sladonja, Barbara; Damijanić, Danijela; Uzelac, Mirela; Poljuha, Danijela (Frontiers in Environmental Science, 2023)
Large and monumental trees are important elements of the ecosystem and represent valuable ecological, environmental, and historical heritage. Different countries have different strategies to protect such trees; most often, through the creation and reference to catalogues of the most valuable, old, big, or monumental trees on the territory. In Croatia, such an inventory has not yet been implemented. In order to create a database and catalogue of super-trees on the territory of Istria, in 2022, we launched a citizen science action to find out the locations of large, old, and valuable trees in Istria with the help of the public. The result of the action is a geo-referenced census of 64 ʻsuper-treesʼ in Istria in the form of an online Catalogue created in ArcGIS StoryMaps application. We proved that it is possible to efficiently and quickly create a catalogue that will serve to protect monumental trees. This Catalogue is the first step in creating a regional or national register.